Career choices for paediatrics: national surveys of graduates of 1974-2002 from UK medical schools. - Turner, G; Lambert, T; Goldacre, M; Turner, S (2007)
BACKGROUND: Knowledge of UK doctors' career intentions and pathways is essential for understanding future workforce requirements. The aim of this study was to report career choices for and career progression in paediatrics in the UK. METHODS: Postal questionnaire surveys of qualifiers from all UK medical schools in nine qualification years since 1974. RESULTS: In total, 74% (24 621/33 412) and 73% (20 720/28 459) of doctors responded at 1 and 3 years after graduation. Choices for paediatrics 1 year after qualifying fell from 7.8% of 1974 graduates to 5.0% of 1983 graduates, increased to 7.2% of 1993 graduates, and since the level has remained fairly constant. Approximately twice the percentage of women graduates than men graduates indicated a long-term career choice for paediatrics. A total of 44% of those who chose paediatrics 1 year after graduation were working in it 10 years after qualifying. Experience of the subject as a student, and enthusiasm/commitment: what I really want to do, affected long-term career choices more for paediatrics than for other medical careers. CONCLUSIONS: The proportion of junior doctors wishing to become paediatricians has not changed much during the last 30 years. The planned increase in the number of medical school graduates is necessary to increase the number of UK-trained consultant paediatricians. Medical students who experience enthusiastic and stimulating training in paediatrics may be more likely to become paediatricians.